(untitled) (Journal of Global Arts Studies, 2023)
Background: Now, personalized cultivation has become a hot topic in the education circle. Objective: The purpose of this paper is to explore the teaching concept of personalized cultivation in the teaching of watercolor landscape sketching. Methods: The case study and text study are discussed from three aspects: Firstly, the common elements in the personalization include the experience of field observation, the relationship between the composition and the black and white rhythm, the harmony of color, the richness and contrast of detail, and the composition and meaning; shape can be cultivated from what aspects: the painting language, interest, materials, ideas, and techniques; finally, discusses how to construct the personalized teaching content framework.. Results: Through the exploratory research results of this paper, it is seen that taking landscape sketching as a way of creation, can not only expand the original concept of sketching, but also develop new ideas for personalized training in teaching; it is conducive to forming diversified teaching outlook, innovative teaching ideas and teaching content system; Conclusions: So it is necessary to carry out the teaching concept in the teaching of watercolor landscape sketching and the practice of personalized training.